2014
DOI: 10.1007/s00277-014-2240-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of first-line treatment with doxycycline in patients with previously untreated ocular adnexal marginal zone B cell lymphoma

Abstract: Ocular adnexal lymphoma (OAL) has been associated with Chlamydophila psittaci infection, for which doxycycline has been suggested as a treatment option. We conducted this study to evaluate the long-term results of first-line doxycycline treatment in patients with OAL. Ninety patients with histologically confirmed OAL with marginal zone B cell lymphoma were enrolled. Each patient received one or two cycles of doxycycline (100 mg bid) for 3 weeks. After a median follow-up period of 40.5 months (8-85), the 5-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…Finally, recent clinical trials with doxycycline and azithromycin (intended to treat cancer-associated infections, but not cancer cells) both show positive therapeutic effects in cancer patients, although their selective effects on eradicating cancer stem cells were not yet known or appreciated [23-26]. These trials were performed on advanced or treatment-resistant patients with B-cell lymphoma (doxycycline) or lung cancer (azithromycin), respectively [23-26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, recent clinical trials with doxycycline and azithromycin (intended to treat cancer-associated infections, but not cancer cells) both show positive therapeutic effects in cancer patients, although their selective effects on eradicating cancer stem cells were not yet known or appreciated [23-26]. These trials were performed on advanced or treatment-resistant patients with B-cell lymphoma (doxycycline) or lung cancer (azithromycin), respectively [23-26].…”
Section: Discussionmentioning
confidence: 99%
“…These trials were performed on advanced or treatment-resistant patients with B-cell lymphoma (doxycycline) or lung cancer (azithromycin), respectively [23-26]. For example, in lung cancers, azithromycin significantly increased 1-year patient survival from 45% to 75%, an ~1.7-fold increase [26].…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From PFS ranged from 55% to 61% in studies demonstrating response. 38,42 Information on C psittaci infection was reported in only 3 of the 9 studies. [38][39][40] Kim et al 40 reported equal responses in patients with C psittaci-positive and negative POAML, while 2 trials from Italy showed better responses in C psittaci-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, response to doxycycline might be influenced by other factors, such as reinfection because of prolonged contact with infected pets . See Table for a selection of studies on antibacterial treatment for ocular adnexal MALT lymphoma …”
Section: Treatmentmentioning
confidence: 99%